Implementasi Ramah Mazhab di Masjid Raya Syekh Ahmad Khatib al-Minangkabawi Sumatera Barat - Azka Ummah; Mahlil Bunaiya (Lembaga Yasin AlSys, 2026)
Religious school diversity within Muslim communities requires an inclusive religious space to strengthen tolerance, coexistence, and social cohesion. This study examines the implementation of the “Ramah Mazhab” approach at the Syekh Ahmad Khatib Al-Minangkabawi Grand Mosque of West Sumatra as a mosque that plays an important role in promoting inter-school tolerance amid a society with strong historical and cultural ties to Islamic law. This study aims to understand the application of the “Ramah Mazhab” concept in encouraging acceptance, respect, and coexistence among various schools of Islamic jurisprudence in Islamic religious practice. This study used a qualitative approach through field observation, interviews with religious figures, and analysis of local religious practices. The results showed that the Syekh Ahmad Khatib Al-Minangkabawi Grand Mosque successfully integrated diverse school-based practices without neglecting the spirit of congregational unity. This inclusive approach contributed to reducing the potential for sectarian conflict, strengthening social cohesion, and enhancing the religious experience of congregants within a more open mosque environment. The conclusion of this study affirms that the implementation of “Ramah Mazhab” at the SAKA Grand Mosque can serve as a model for managing religious institutions that are responsive to school-of-jurisprudence diversity. The implications of this study indicate the importance of strengthening inclusive religious approaches for mosques and other Islamic institutions in building harmony, tolerance, and Muslim unity amid diverse Muslim communities.